2022
DOI: 10.1021/acsapm.1c01581
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Adsorption of Toxic Substances from Cigarette Smoke Using Nanocellulose-SiO2 Hybrid Aerogels

Abstract: A cellulose nanofiber-SiO2 hybrid aerogel cigarette (CSG) filter, which can be used for ultrahigh adsorption of toxic substances from cigarette smoke, was prepared based on the skeletal material of cellulose nanofibers (CNFs) with the help of a simple directional frozen technology. SEM and FTIR results confirmed the successful introduction of the SiO2 nanoparticles, and the application process of SiO2 nanoparticles did not influence the three-dimensional network structure of CSGs. Considering the practical app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…After three adsorption cycles and cleaning, the FT-IR spectra of the UiO-66@CF materials and the characteristic band of the composite material were retained, and it was found that the peaks at 2918 and 2856 cm –1 disappeared after cleaning, which further proved the recyclability of the material (Figure S18b). Furthermore, UiO-66@CF was compared with other reported functionalized filters (Table S3), indicating that the nicotine adsorption efficiency of UiO-66@CF was higher than other materials. Moreover, the cost of UiO-66@CF as the filter was relatively cheaper than other reported materials (Table S4).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…After three adsorption cycles and cleaning, the FT-IR spectra of the UiO-66@CF materials and the characteristic band of the composite material were retained, and it was found that the peaks at 2918 and 2856 cm –1 disappeared after cleaning, which further proved the recyclability of the material (Figure S18b). Furthermore, UiO-66@CF was compared with other reported functionalized filters (Table S3), indicating that the nicotine adsorption efficiency of UiO-66@CF was higher than other materials. Moreover, the cost of UiO-66@CF as the filter was relatively cheaper than other reported materials (Table S4).…”
Section: Resultsmentioning
confidence: 97%
“…This can be explained by a diminished crystallinity of cellulose given the interaction of MOFs particles with free hydroxyl groups on the surface of cellulose fiber. 45 Among the prepared samples, UiO-66@CF presents the best flexibility and can bend without the formation of cracks observable by naked eyes. Additionally, it was also found that the toughness of the MOF@CF samples increased but the rigidity decreased after incorporating MOF particles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al. [ 44 ] developed a CSG aerogel cigarette filter prepared using cellulose nanofibers modified with SiO 2 nanoparticles and investigated its adsorption properties for toxic substances. Compared to the conventional CAF, the CSG filter exhibited superior adsorption capacity for hazardous substances present in cigarette smoke, with removal rates of 92.2% (tar), 90.3% (total particulate matter, TPM), 95.0% (nicotine), and 20.6% (CO).…”
Section: Advanced Materials Design For the Adsorption Of Toxic Substa...mentioning
confidence: 99%
“…However, among traditional cigarette filters, such as cellulose acetate cigarette filters, polypropylene cigarette filters, and polylactic acid cigarette filters, either low filtration efficiency or nondegradability cannot meet the current need for smoke filters. Consequently, to adsorb toxic chemicals from smoke, large amounts of functional purification materials are explored, such as silica, zeolites, graphene and oxidized carbon nanocages, etc. Huang’s group investigated a nicotine surface-imprinted monolith for the selective removal of nicotine from smoke, and it exhibited a high adsorption performance with an adsorption efficiency of 99.43% .…”
Section: Introductionmentioning
confidence: 99%